BRIC-Investitionen in Deutschland Chancen und Risiken für Unternehmen und Arbeitnehmer - Franz, Martin; Henn, Sebastian; Weingarten, Jörg (Forschung aus der Hans-Böckler-Stiftung, 2016)
This study analyzes structures, strategies and effects on employment of direct investments from BRIC countries - and sets prejudices about foreign investment straight.